Seismic Performance Analysis of Fabricated Concrete Beam-Column Joints Based on Intelligent Finite Element Analysis - Chen Yang; Xiancheng Li (Journal of Electrical and Computer Engineering)
In order to improve the seismic performance analysis effect of prefabricated concrete beam-column joints, this article uses intelligent finite element analysis technology to analyze the seismic performance of prefabricated concrete beam-column joints. Moreover, this article conducts in-depth research on the shear bearing capacity of the plastic hinge area so as to improve the accuracy of the calculation of the shear bearing capacity of the plastic hinge area. In addition, this article conducts finite element analysis of integral frame joints, uses finite element software to carry out numerical simulation of frame joints, and compares and analyzes the experimental results in the literature. Further, this article proposes an improvement of a prefabricated frame joint, performs finite element analysis on it, and compares and analyzes the numerical simulation results of concrete joints. The analysis results show that the finite element analysis model proposed in this article has high accuracy in the seismic performance analysis of prefabricated concrete beam-column joints, which meets the actual needs of the seismic performance analysis of modern prefabricated concrete beam-column joints.